Toleransi Pelencengan Arah Kiblat di Indonesia Perspektif Ilmu Falak dan Hukum Islam - Zulfiah; Ismail Ismail; Dikson T. Yasin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2021)
This study discusses the limits of deviation of the direction of qibla that is allowed in facing the direction of qibla in Indonesia. This study uses qualitative descriptive analysis with an astronomical approach and Islamic law approach. The results show that there are two types of tolerance towards the qibla, namely mathematical tolerance, and sociological tolerance. Mathematically, tolerance lies in the ability to face three directions, namely the direction of the Ka'bah, the direction of the holy mosque, and the direction of the forbidden land. Sociologically, the deflection tolerance of the direction of qibla 6 ° bows to the left of the Ka'bah or the right of the Ka'bah. Mathematical qibla direction tolerance is provided for the construction of places of worship such as mosques and small mosques, while sociological of Islamic Law, qibla tolerance is allocated for people who perform prayers.